Who benefits from RCEP? Application of trade policy tools - Francis Mark A. Quimba; Mark Anthony A. Barral; Abigail E. Andrada (Philippine Institute for Development Studies (PIDS), 2021)
The Regional Comprehensive Economic Partnership Agreement (RCEP) gathers 10 ASEAN countries and five partners, namely, the Republic of Korea, China, Japan, New Zealand, and Australia. RCEP covers a market of 2.2 billion consumers and accounts for more than 30 percent of the global GDP. The agreement was signed last November 15, 2020 through a video conference with the abovementioned countries. RCEP is the largest free trade agreement and can be a catalyst for economic development for the Philippines. However, there are economic and political concerns being raised against RCEP. This paper contributes to the discussion on RCEP by providing a policy tool that calculates the impact of the trade agreement on exports and GDP. The calculations show that RCEP has a positive impact on Philippine exports and GDP. Other top gainers would be Vietnam and Korea.
Keywords: 330; regional integration; digital; sustainable development; trade